Film Animasi “Kanca Cilik” Sebagai Intervensi dalam Perilaku Mencari Bantuan Kesehatan Jiwa Pada Usia Remaja - Lani Tiara Karlina Putri; Ahmad Guntur Alfianto; Rahmania Ramadhani (Jurnal Kesehatan Medika Udayana, 2023)
Background: Post-adolescent mental health problems in Indonesia are currently experiencing an increase from 2013 to 2018. Efforts and forms of intervention that can be carried out are through increasing the behavior of seeking mental health assistance. Such efforts can be health promotion. Proper health promotion for adolescent with film media. the animated film "Kanca Cilik" is a medium to promote the behavior of seeking mental health assistance in adolescents. Purpose: The purpose of this research is to develop the animated film "Kanca Cilik" as an intervention for adolescents in seeking mental health assistance. Method: The method used by developing two stages. The first stage is to make an animated film "Kanca Cilik" with 3 episodes and an average duration of 3 minutes/episode. Then in the second stage, a perception test was carried out on mental health nurses, community, and animation experts. The test results use the Intraclass Correlation Coefficients (ICC) test. Result:  The result of this development research is the animated film "Kanca Cilik" which consists of three episodes, namely the first episode is behavior seeking mental health assistance from peers, the second episode is behavior seeking mental health assistance to family and the last episode is behavior seeking mental health assistance to professionals. . statistical analysis was obtained at 0.896 and the average value of the 3 reviewers was 0.978> 0.5 (high stability). Conclusion: The conclusion of this study is that the film "Kanca Cilik" as a behavior intervention seeking mental health assistance in adolescents is good for use as an effort to promote mental health. and suggestions for this research to be used as an intervention in increasing mental health seeking behavior in adolescents.